1997
DOI: 10.1007/bf02083304
|View full text |Cite
|
Sign up to set email alerts
|

Searching for migraine genes: exclusion of 290 cM out of the whole human genome

Abstract: A linkage and association analysis was made on 14 Italian families with recurrent migraine. We analyzed five chromosomal regions surrounding the candidate genes 5HT1D (1p36.3-34.3), 5HT1B (6q13), 5HT2A (13q14-21), 5HT transporter (17q11.2-12), CACNLB1 (17q11.2-22) and FHM (19p13), using 29 DNA polymorphic markers. All two-point lod scores were negative, and the chi 2 sib-pair analyses were not significant, thus indicating the probable exclusion of these regions as sites of migraine genes in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
4
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
2
13
4
1
Order By: Relevance
“…The only study to report a significant association with migraine involved genetic variants of the 5-HT transporter SERT gene, in which an overrepresentation of allele Stin2.12 and a reduction of allele Stin2.10 were found in MO, with an additional trend to overrepresented Stin 2.9 allele in MA [39]. Exactly the opposite (increased Stin2.10 allele in migraine) was found by Yilmaz et al [40], however, and negative findings were reported both by us in our sample of 14 Italian families with migraine [15] and by Lea et al [41].…”
Section: Migraine and The Mitochondrial Genomecontrasting
confidence: 51%
See 2 more Smart Citations
“…The only study to report a significant association with migraine involved genetic variants of the 5-HT transporter SERT gene, in which an overrepresentation of allele Stin2.12 and a reduction of allele Stin2.10 were found in MO, with an additional trend to overrepresented Stin 2.9 allele in MA [39]. Exactly the opposite (increased Stin2.10 allele in migraine) was found by Yilmaz et al [40], however, and negative findings were reported both by us in our sample of 14 Italian families with migraine [15] and by Lea et al [41].…”
Section: Migraine and The Mitochondrial Genomecontrasting
confidence: 51%
“…They excluded a region of 50 cM, flanking the FHM locus as a site of migraine liability. In our own study of 14 Italian families with MO and MA, we performed association, linkage and sib-pair analyses to markers near the CACNA1A region, with negative results [15]. In another study of Italian familial cases of "complicated" migraine, migraine stroke and MA [16], we reported the absence of the four original CACNA1A mutations described in FHM by Ophoff et al [17].…”
Section: Migraine As a Channelopathymentioning
confidence: 99%
See 1 more Smart Citation
“…However, an attempt to identify the chromosomal locations of the candidate genes 5-HT 1D (1p36.3-34.3), 5-HT 1B (6p13), 5-HT 2A (13q14-21), 5-HT transporter (17q11.2-12), CACNLB1 (17q11. and FHM locus (19p13) was failed [24] .The 11084 A to G base substitution was not confirmed to be the gene for the ND4 subunit of respiratory complex 1 as found in 25% of Japanese migraineurs [25] and the mutation of this gene was not associated with the migraine in Denmark. No differences or trends in allele or genotype frequencies of 5-HT 2C receptor gene were found in migraineurs [9] .…”
Section: Genes Associated With Migrainementioning
confidence: 91%
“…Linkage studies have predictably proved negative [20]. Surprisingly, in view of the female preponderance of migraine, Nyholt et al [19] identified a linkage with the X chromosome (Xq24-28) in 2 families.…”
Section: Familial Hemiplegic Migrainementioning
confidence: 99%